Censuses and cattle in Antioquia (New Kingdom of Granada): Methods for a livestock history in the late 18th century - Gómez Gómez, Mauricio Alejandro (Huarte de San Juan. Geografía e Historia, 2020)
This article studies the social history of livestock and their owners in Antioquia at the end of the 18th century. The source is the censuses ordered by the visitor Juan Antonio Mon y Velarde between 1786 and 1787. The quantitative analysis contrasted with qualitative records, such as visits, mortuaries and lawsuits, allowed to recognize links between the possession of certain livestock, the socio-economiclevel and the forms of social distinction and exclusion. The history of domestic animals tells us unknown aspects of their owners, their aspirations, symbolisms, choices and life conditions.
Keywords: Social history; colonial history; domestic animals; Bourbon reforms